Dynamics of mental health in childhood - E. A. Kozlova; H. R. Slobodskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The longitudinal study examined continuity of child mental health problems (n = 70) using parent reported Child Behavior Checklist (CBCL /1 /½-5) in early childhood and the Strengths and Difficulties Questionnaire (SDQ) in preschool and school age. Longitudinal correlations and multiple regression indicated that sleep problems predicted higher levels of mental health problems, emotional symptoms showed homotypic continuity, and impact of psychiatric problems was predicted by earlier total problems, particularly externalizing and attention problems; the models explained from 10 to 12% of the variance in subsequent child mental health problems.